Medicinal plants as potential anti-cholesterol agents: a narrative review of in vivo, in vitro, and in silico evidence - Made Suta Wahyudi; Luh Putu Mirah Kusuma Dewi; Ni Made Pitri Susanti (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2025)
Background: Hypercholesterolaemia is a major cardiovascular risk factor commonly managed with statins, which are frequently associated with hepatotoxicity, myopathy, and new-onset diabetes mellitus, driving interest in medicinal plants as natural alternatives. Objective: This review aimed to identify medicinal plants with demonstrated or predicted anti-cholesterol activity, specifying plant species, plant parts, and evidence from in vivo, in vitro, and in silico studies. Methods: A narrative literature review was conducted following PRISMA 2020 guidelines. Original articles published between 2014 and 2024 were retrieved from Google Scholar, Google, and PubMed. Review articles and studies unavailable in full text were excluded. Results: Nineteen articles met the eligibility criteria. Fourteen medicinal plants demonstrated cholesterol-lowering activity in in vivo and in vitro studies. Five plants were assessed in silico; quercetin-type flavonoids from karamunting, sweet orange, and soursop showed binding free energies more favourable than statin controls against HMG-CoA reductase, while butterfly pea and water clover compounds did not surpass their controls. Conclusion: Extracts from kirinyuh, ceremai, and ketapang achieved notable cholesterol reductions at low effective doses in animal models. Green kiwi fruit extract showed the greatest in vitro potency (EC50 = 7.3 ppm). In silico findings are preliminary and require experimental validation. Further research should isolate active compounds and evaluate efficacy through clinical studies in humans.